Sub‐Nanometer Porous Carbon Materials for High‐Performance Supercapacitors Using Carbon Dots as Self‐templated Pore‐Makers - Zhang, Xi‐Rong; Song, Tian‐Bing; He, Tian‐Le; Ma, Qian‐Li; Wu, Zhao‐Fan; Wang, Yong‐Gang; Xiong, Huan‐Ming (Advanced functional materials, 2025)
Customizable porous carbon structures are critical for high‐performance electrode materials, and the modulation of the pore parameters at different levels remains a great challenge. For supercapacitors, the preferred carbon materials should own high specific capacitance, nice rate performance, large density, low self‐discharge, and high mass‐loading, which could be accomplished by sub‐nanometer pores (0.5–1.0 nm). Herein, a new method of using carbon dots (CDs) as self‐templates is reported to produce porous carbon with uniform pore diameters of 0.64–0.80 nm. As a result, the optimal sample with a high packing density (0.81 g cm−3) displays outstanding capacitances (gravimetric 515.5 F g−1, areal 5.16 F cm−2, and volumetric 417.6 F cm−3 respectively at 1 A g−1) at the commercial‐level mass‐loading of 10 mg cm−2. The assembled high‐loading symmetric supercapacitor shows a high energy density of 22.3 Wh kg−1 at 3500 W kg−1, as well as a long cycle stability (99.9% of retention rate after 10 000 cycles at 2 A g−1) in an ultrawide voltage range of 1.4 V with aqueous electrolytes. This work suggests a micropore‐forming strategy for the preferred porous carbon, which can be applied in supercapacitors, batteries, filters, adsorbents, and catalysts. The well‐designed carbon dots are used as self‐templates to produce porous carbon with uniform pore diameters of 0.64–0.80 nm and high surface areas, which benefit ion storage in supercapacitors and result in excellent electrochemical performances.